Biomimetic Morphogenesis of Strontium Chitosan-Gelatin Composite Aggregates via EPD and Biomineralization in vitro and in vivo - Gong L; Jiang T; Xiao T; Feng B; Wei M; Liu C; Xiao W; Huang P; Huang D (International Journal of Nanomedicine, 2024)
Lingling Gong,1,2 Tao Jiang,3,4 Ting Xiao,1,2 Bo Feng,1,2 Mouda Wei,5 Chuanzi Liu,3 Weiwei Xiao,1,2 Pin Huang,5 Dan Huang6– 8 1Department of prosthodontics, Changsha Stomatological Hospital, Changsha, Hunan, People’s Republic of China; 2Department of prosthodontics, School of Stomatology, Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of China; 3The State Key Laboratory Breeding Base of Basic Science of Stomatology (Hubei- MOST) & Key Laboratory of Oral Biomedicine Ministry of Education, School & Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China; 4Department of Prosthodontics, Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China; 5Department of Pediatric Dentistry, Ubcare Dental Clinic Co. Ltd, Changsha, Hunan, People’s Republic of China; 6Department of Stomatology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 7Department of Prosthodontics and Implantology, School of Stomatology, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 8Hubei Province Key Laboratory of Oral and Maxillofacial Development and Regeneration, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaCorrespondence: Pin Huang, Department of Pediatric Dentistry, Ubcare Dental Clinic Co. ltd, 768 Xiangzhang Road, Yuhua District, Changsha City, Hunan province, People’s Republic of China, Email huang.pin@outlook.com Dan Huang, Department of Stomatology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095 Jiefang Avenue, Wuhan, Hubei, People’s Republic of China, Email Huangdan@tjh.tjmu.edu.cnIntroduction: Biomineralization has been increasingly adopted for the synthesis of advanced materials with superior properties. Hierarchical architecture growth mimicking biomineralization has been studied using various organic molecules to template inorganic materials with controlled morphology. In our previous study, self-assembled Sr/CS/G(SrCO3-chitosan-gelatin) aggregates were fabricated using electrophoretic deposition (EPD). This study is a further step toward understanding the morphogenesis of Sr/CS/G aggregates and its biomineralization.Methods: Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) were used to investigate the biomimetic morphogenesis of Sr/CS/G composite under various EPD parameters, such as polymer concentration, time, and voltage. The Sr/CS/G aggregates were immersed in H2O, phosphate-buffered saline (PBS), and simulated body fluid (SBF) to study the bioactive apatite formation ability. In addition, biocompatibility of the composites were evaluated by Fluorescence staining, SEM in vitro. The osteogenic ability of the coatings induced by PBS were tested in vivo.Results: The CS/G weight ratio, EPD time, and voltage were found to influence the morphogenesis of Sr/CS/G aggregates. SEM and TEM results showed that the Sr/CS/G aggregates exhibited fractal growth characteristics and morphological self-similarity. XRD results confirmed the formation of SrCO3 crystals within the framework of chitosan and gelatin organic templates. Chitosan played a vital role in branching growth of the crystals, whereas gelatin guided the formation of composite spheres. The microstructural and compositional results reveal that the Sr/CS/G-induced apatite coating yielded a large quantity of apatite. These apatite coatings promote the cytocompatibility and osteogenesis of rat bone marrow mesenchymal stem cells (rBMSCs) in vitro. The coatings induced by PBS enhanced proliferation and mineralization in vitro, and enhanced angiogenesis and osteogenesis in vivo.Conclusion: Sr/CS/G composites prepared via EPD are promising organic-inorganic templates for biomineralization. These findings provide important insights into understanding the mineralization process and optimizing the design of advanced biological materials.Keywords: biomineralization, EPD parameter, Sr/CS/G aggregates, morphogenesis, hydroxyapatite